GaLactic and Extragalactic All-sky Murchison Widefield Array (GLEAM) survey II: Galactic plane 345° < l < 67°, 180° < l < 240°. (2019) - Hurley-Walker, N.; Hancock, P. J.; Franzen, T. M. O.; Callingham, J. R.; Offringa, A. R.; Hindson, L.; Wu, C.; Bell, M. E.; For, B.-Q.; Gaensler, B. M.; Johnston-Hollitt, M.; Kapińska, A. D.; et al.
Abstract: This work makes available a further $2\, 860~\text{deg}^2$ of the GaLactic and Extragalactic All-sky Murchison Widefield Array (GLEAM) survey, covering half of the accessible galactic plane, across 20 frequency bands sampling 72–231 MHz, with resolution $4\, \text{arcmin}-2\, \text{arcmin}$ . Unlike previous GLEAM data releases, we used multi-scale CLEAN to better deconvolve large-scale galactic structure. For the galactic longitude ranges $345^° < l < 67^°$, $180^° < l < 240^°$, we provide a compact source catalogue of 22 037 components selected from a 60-MHz bandwidth image centred at 200 MHz, with RMS noise $≈10-20\, \text{mJy}\, \text{beam}^{-1}$ and position accuracy better than 2 arcsec. The catalogue has a completeness of 50% at ${≈}120\, \text{mJy}$, and a reliability of 99.86%. It covers galactic latitudes $1^°≤|b|≤10^°$ towards the galactic centre and $|b|≤10^°$ for other regions, and is available from Vizier; images covering $|b|≤10^°$ for all longitudes are made available on the GLEAM Virtual Observatory (VO).server and SkyView.